Improvement of Hand Hygiene Practices among the Healthcare Workers in a Neonatal Intensive Care Unit - Abdullahel Amaan; Sanjoy Kumer Dey; Khainoor Zahan (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Healthcare workers’ (HCWs) hands become progressively colonized with potential pathogens during their patient care and act as a vehicle for transmission of microorganisms to other patients. Hand hygiene is undisputedly one of the most effective infection control measures. The objective of this study was to measure the hand hygiene (HH) compliance among the doctors and nurses before and after intervention. Methodology. This quasi-experimental (before and after) study was conducted from July 2019 to July 2020 in the neonatal intensive care unit in a tertiary hospital in Bangladesh. The doctors and nurses were observed for their compliance to HH before and after the intervention. Several group discussions were arranged, and posters on HH were attached as reminders at the workstations during the intervention period. Binary logistic regression analysis of the predictors for the outcome as HH noncompliance was performed. Result. The overall compliance to HH was significantly increased in both before (from 42.9 to 83.8%, p=<0.0001) and after (28.5 to 95.9%, p=<0.000) patient contact, in both the case of high-risk and low-risk contacts (p=<0.000) following the intervention. A significant reduction in the frequency of inadequate HH (20.2 to 9.7%, p = .000) was documented. In logistic regression analysis, compliance to HH was found more after the intervention (aOR = 13.315, 95% CI: 7.248–24.458). Similarly, being a physician (aOR = 0.012, 95% CI: 0.005–0.030) and moments after patient contact (aOR = 0.114, 95% CI: 0.049–0.261), significant positive predictors for compliance to HH were found. Conclusion. Significant improvements in HH compliance were achieved through a systemic, multidimensional intervention approach among the doctors and nurses in an intensive newborn care setting.